RISK ANALYSIS OF THE PILLAR STRENGTH IN THE ESTONIA MINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper deals with the risk analysis and assessment of the pillars strength problems in the Estonia oil shale mine. Aim of this investigation was to determine the strength parameters and predict the bearing capacity of the pillars in Estonia mine, mining block No. 3107 Methods were based on theoretical investigation and experimental data of in-situ conditions. It is given the geological description of the mining block and determined the strength parameters, moisture content and volume density of the oil shale and limestone layers. Analysis showed that the used risk analysis method is applicable for Estonian oil shale mines. The results of the risk analysis are of particular interest for practical purposes.